RANCANG BANGUN SISTEM PENDETEKSI KEBAKARAN HUTAN BERBASIS NODE MCU ESP8266 - I G A Ari Kukuh Sentanu; I Gst A. Komang Diafari Djuni; Nyoman Pramaita (Program Studi Teknik Elektro UNUD, 2021)
The problem that often occurs so far is the delay in the presence of the fire departmentat the fire site. So the authors make an early detection tool for forest fires based on the Internetof Things because forest fires occur in very large forests so that supervision from officers is notenough. This study aims to design a forest fire extinguishing system based on ESP8266NodeMCU. The research was conducted by designing a system and making it happen by usinga board and several sensors to obtain data. From the results of the design carried out in thisstudy, the prototype of forest fire detection systems based on NodeMCU ESP8266 andtemperature, fire and smoke sensors has been realized, which can send notifications ontelegram. And the pump can put out the fire. The actual application in the forest still needschanges to the pump construction and the addition of several sensors.